Telemedicine-Supported Exercise Interventions in Hematopoietic Stem Cell Transplantation: A Scoping Review - Gonçalves Leite Rocco P; Reategui-Rivera CM; Finkelstein J (International Journal of General Medicine)
Patricia Gonçalves Leite Rocco,1 C Mahony Reategui-Rivera,2 Joseph Finkelstein1 1Arizona Telemedicine Program, College of Medicine - Tucson, University of Arizona, Tucson, AZ, USA; 2Department of Biomedical Informatics, School of Medicine, University of Utah, Salt Lake City, UT, USACorrespondence: Joseph Finkelstein, Arizona Telemedicine Program, College of Medicine - Tucson, University of Arizona, 1501 N Campbell Ave, AHSL 1156, Tucson, AZ, 85724, USA, Tel +1-520-626-3944, Fax +1-520-626-6020, Email jfinkelstein1@arizona.eduBackground: Hematopoietic stem cell transplantation is a potentially curative therapy for various hematologic conditions. Though physical exercise has been shown to positively affect physical and psychosocial function in patients undergoing hematopoietic stem cell transplantation, they often face multiple barriers to accessing comprehensive exercise-based rehabilitation programs. Telemedicine has emerged as a promising strategy to overcome these challenges by facilitating remote exercise interventions and potentially improving patient outcomes.Objective: This scoping review aimed to map the current landscape of telemedicine-supported exercise interventions in hematopoietic stem cell transplantation, assessing their clinical and technical characteristics, feasibility, effectiveness, and gaps in the literature.Methods: Following the Arksey and O’Malley framework and subsequent enhancements, we systematically searched MEDLINE, SCOPUS, Web of Science, and Embase from inception to July 31, 2024. We included experimental studies examining telemedicine-supported exercise interventions for hematopoietic stem cell transplantation recipients and extracted data on study design, participant characteristics, technology used, exercise modalities, and outcomes measured. Findings were synthesized narratively.Results: Our search resulted in 1116 papers, with 10 included in the final review. Most studies (90%) focused on feasibility and employed prospective designs, including quasi-experimental (60%) and randomized controlled trials (40%). Sample sizes were generally small, with 80% of studies enrolling fewer than 50 participants. Aerobic exercise was the most frequently implemented modality (80%), with reported improvements in VO2peak, 6-minute walk test performance, and quality of life. Functional outcomes were assessed in 90% of studies, while 50% evaluated quality-of-life metrics. Interventions were largely feasible, safe, and acceptable, overcoming barriers to care for hematopoietic stem cell transplantation patients.Conclusion: Telemedicine-supported exercise interventions are feasible and show promise in improving physical function and quality of life for hematopoietic stem cell transplantation patients.Keywords: telemedicine, hematopoietic stem cell transplantation, telerehabilitation, exercise, scoping review